Can micro-credit support public health subsidy programs? - Britta Augsburg; Bet Caeyers; Bansi Malde (Institute for Fiscal Studies (IFS), 2019)
The low take-up of cost-effective and highly subsidised preventive health technologies in low-income countries remains a puzzle. One under-studied reason is that the design of subsidy schemes is such that households remain financially constrained. In this paper we analyse whether, and how, micro-finance supports a large public health subsidy program in the developing world - the Swachh Bharat Mission - in achieving its aim of increasing uptake of individual household latrines. Exploiting a cluster randomised controlled experiment of a sanitation micro-finance program that coincided with the launch of the SBM program, and unique survey data matched to administrative data, we find that the complementarity runs on two levels: First, micro-credit allows households officially ineligible for the subsidy to invest in sanitation by alleviating credit constraints. Second, micro-credit also helps subsidy eligible households to overcome short-term liquidity constraints induced by the remuneration-post-verification subsidy design to invest in sanitation. Subsidy eligible households living in areas experiencing large delays in subsidy disbursement, or high toilet costs, are more likely to take a sanitation loan, but less likely to use the loan to construct a toilet.
Keywords: D14; G41; H24; I12; I38; O16; 330